Adaptive Technology for Special Education: Enhancing IEP Development and Delivery - Shakhnoza Khaydarova PhD (Periodica Journal, 2024)
Adaptive technology is transforming the landscape of special education, particularly in the development and implementation of Individualized Education Programs (IEPs), by offering personalized learning experiences, improving collaboration, and enabling precise progress monitoring. This article explores the role of adaptive technology, its impact on IEPs, and its potential to create more inclusive learning environments.
Keywords: Adaptive Technology; Special Education; Individualized Education Programs